2021
DOI: 10.1186/s12933-021-01274-x
|View full text |Cite
|
Sign up to set email alerts
|

Stronger association of triglyceride glucose index than the HOMA-IR with arterial stiffness in patients with type 2 diabetes: a real-world single-centre study

Abstract: Background The triglyceride-glucose index (TyG index) has been proposed as a simple and reliable alternative insulin resistance (IR) marker, while the homeostasis model assessment for IR (HOMA-IR) is the most frequently used index. Few studies have evaluated the role of IR assessed by the TyG index and HOMA-IR on arterial stiffness in a type 2 diabetes (T2D) population with a high risk of increased arterial stiffness. We aimed to investigate the association of the TyG index and HOMA-IR with art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 52 publications
(31 reference statements)
6
119
0
Order By: Relevance
“…Given the diminished reliability of baPWV measurement in subjects with severe atherosclerosis in lower extremities ( 7 ), we excluded subjects with bilateral ABIs < 0.9, for subjects with unilateral ABI < 0.9, we recorded contralateral baPWV, and for subjects with no ABI < 0.9, the mean of right and left baPWV was recorded for the analysis. Additionally, we defined high baPWV as a value greater than the 75th percentile of the baPWV values, which was 2,248 cm/s in this study ( 16 , 19 , 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the diminished reliability of baPWV measurement in subjects with severe atherosclerosis in lower extremities ( 7 ), we excluded subjects with bilateral ABIs < 0.9, for subjects with unilateral ABI < 0.9, we recorded contralateral baPWV, and for subjects with no ABI < 0.9, the mean of right and left baPWV was recorded for the analysis. Additionally, we defined high baPWV as a value greater than the 75th percentile of the baPWV values, which was 2,248 cm/s in this study ( 16 , 19 , 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies indicated that IR assessed by the TyG index is associated with arterial stiffness measured by the baPWV ( 16 22 ); however, discrepancies remain due to study population, sample size, and potential confounders. In this study, we investigated the association between the TyG index and the baPWV in a population of Chinese community-dwelling elderly.…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19] Different from HOMA-IR, the TyG index was universally adaptable in all patients due to the calculation without quantification of insulin. 20,21 It was well distinguished that an increased TyG index would contributing to diagnosing T2DM and predicting related adverse outcomes. 22,23 Kidney as a metabolic organ is easy to be damaged by glucose metabolism disorders and diabetic nephropathy has been considered as a huge burden in population.…”
mentioning
confidence: 99%
“…In addition, a large number of studies have shown that the TyG index is closely related to vascular calcification [ 41 – 43 ], and arterial stiffness assessed by pulse wave velocity [ 44 , 45 ], both of which were important risk predictors for ASCVD. Moreover, the association between the TyG index and a variety of risk factors for ASCVD, for example, hypertension [ 46 ], renal dysfunction [ 47 ], and hyperuricemia [ 48 ], was also confirmed by previous studies.…”
Section: Discussionmentioning
confidence: 99%